The main aspects of medical supply in armed forces of NATO member countries - M. V. Bilous; O. P. Shmatenko; O. A. Ryzhov; D. V. Drozdov (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2016)
Introduction. Nowadays medical supply system of Ukrainian military men does not fully correspond to the current needs of the troops, and has to be improved. Further direction of Ukrainian Armed Forces development demands functioning medical service on the ground of logistics management concept.